The selective and meticulous use of color in cinema: Enhancing the emotional and dramatic values in the narrative - Neves, Jaime (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In the first half of the 20th century, the arrival of color in cinema gives it a new and very relevant power. The psychological and affective signifiers of the most varied colors, if properly applied, can give the cinematographic work an extraordinary narrative involvement that provokes a strong affective and dramatic impact on the spectator. Throughout this work, we intend to reflect on the possibilities that color has brought to the cinema, going beyond aesthetics and assuming a prominent position in the field of narrative.